Fungsi Utilitas Barang Halal - Rinda Rosmala (Institut Agama Islam Agus Salim Metro Lampung, 2020)
Abstract The goal of consumers is to find the highest satisfaction. Determination of goods or services for consumption is based on satisfaction criteria. The consumption limit is only budgetary capacity. As long as there is a budget to buy goods or services, then these items will be consumed. In other words, as long as the consumer has income, nothing can prevent him from consuming the desired item. This attitude will clearly deny consideration of the interests of others or consideration of other aspects such as halal. Such consumer behavior, of course, cannot be taken for granted in the Islamic economy. Islamic consumption is always guided by Islamic teachings. As we know that Islam is very concerned about the quality and sanctity of consumer goods manifested in the Koran and Al-Hadith. This is not only transcendental, but also mundane because Islam is very concerned about the sanctity and cleanliness of consumer goods, so this paradox encourages us to understand that satisfaction of a Muslim is very much determined by the level of halalness and the level of prohibition of consumer goods. Assumptions and axioms in Islam are the emphasis on halal, haram, and blessings of the goods to be consumed. So if an individual is faced with two choices A and B, then a Muslim will choose goods that have a higher level of halal and blessing, even though other items are physically preferred. Although the type of relationship that will be explored is substitute, Islam prohibits the substitution (substitution) of goods or transactions that are lawful with goods or illegitimate transactions. Keyword: Utilitas Axioms In Islam, Halal, Haram, Blessings